2007
DOI: 10.1271/bbb.70003
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Single Membrane Component from theBacillus merOperon Enhanced Mercury Resistance in anEscherichia coliHost

Abstract: Overexpression of a mercuric ion binding protein, MerP, from the mercury resistance operon genes of Gram-positive bacterial strain Bacillus megaterium MB1 and from Gram-negative bacterial strain Pseudomonas aeruginosa K-62 was found to enhance the mercury resistance level of Escherichia coli host cells, even though they share only 27.3% identity. Immunoblot analysis showed that MerP (BMerP) from Bacillus could be expressed on the membrane fraction of E. coli cells. Treated with 10 microM Hg2+, a recombinant st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
4
0
1
Order By: Relevance
“…Its adsorption efficiency was 7-fold higher than the control Top10/pBAT1, with 100% of Hg 2+ ranging from 0.1 to 100 nM adsorbed. This adsorption efficiency was higher than the genetically engineered bacteria E. coli strains overexpressed a single membrane component from a Bacillus mer operon (BMerP) and a tilapia metallothionein (tMT), which showed 27 and 25% increase in Hg 2+ adsorption efficiency [47,48]. Since no cysteine presented in the amino acid sequence, Gst Pm -4 may adsorb Hg 2+ via several charged surface functional groups like carboxyl, amino, carbonyl and hydroxyl that could interact with Hg 2+ through ion exchange and complex formation [42,49].…”
Section: Discussionmentioning
confidence: 89%
“…Its adsorption efficiency was 7-fold higher than the control Top10/pBAT1, with 100% of Hg 2+ ranging from 0.1 to 100 nM adsorbed. This adsorption efficiency was higher than the genetically engineered bacteria E. coli strains overexpressed a single membrane component from a Bacillus mer operon (BMerP) and a tilapia metallothionein (tMT), which showed 27 and 25% increase in Hg 2+ adsorption efficiency [47,48]. Since no cysteine presented in the amino acid sequence, Gst Pm -4 may adsorb Hg 2+ via several charged surface functional groups like carboxyl, amino, carbonyl and hydroxyl that could interact with Hg 2+ through ion exchange and complex formation [42,49].…”
Section: Discussionmentioning
confidence: 89%
“…The steps involved in the mer -mediated reduction of Hg(II) by Gram-positive microbes might include (Figure A; see also supporting text S3.21−S3.23): (1) diffusion of neutral Hg(II) species across the diffusion boundary layer (DBL) with a thickness similar to the cell’s radius, (2) uptake of Hg(II) across the murein layer of the Gram-positive cell wall possibly involving MerP , (3) transfer of Hg(II) to MerT (or an alternative transmembrane transporter) and transport across the cell membrane to -SH rich groups in the cytoplasm or the N-terminal domain of MerA , (4) MerA-mediated Hg(II) reduction, (5) diffusion of volatile and lipid-soluble Hg(0) across the cell membrane, and (6) diffusion of Hg(0) across the liquid−gas interface.…”
Section: Resultsmentioning
confidence: 99%
“…Specific, high-affinity, and dedicated uptake of Hg(II) is initiated in the bacterial periplasm (in Gram-negative bacteria) where MerP acts as an extracytoplasmic Hg(II) "sponge" that transfers the Hg(II) ion to transmembrane R-helical transporters such as MerT, which then transports it across the inner membrane. It has been suggested that in Gram-positive bacteria, which lack both the outer membrane (OM) and a "proper" periplasmic space, MerP is present outside the cell but attached to the cytoplasmic/inner membrane (6).…”
Section: Introductionmentioning
confidence: 99%
“…The lysate was centrifuged at 4°C, at 10,000 g for 10 min to remove unbroken cells. The supernatants were then centrifuged (Beckman L8-70 M) at 4°C, at 30,000 rpm for 30 min (Hsieh et al 2007). Pellets were digested with concentrated HNO 3 and separately used to estimate the biosorbed metal concentration by using ICP-OES (Perkin Elmer, Optima 2100 DV).…”
Section: Effect Of Metal Ion Concentration On Bioaccumulationmentioning
confidence: 99%